2020
DOI: 10.1111/epi.16657
|View full text |Cite
|
Sign up to set email alerts
|

Cortex leads the thalamic centromedian nucleus in generalized epileptic discharges in Lennox‐Gastaut syndrome

Abstract: We aimed to assess the roles of the cortex and thalamus (centromedian nucleus [CM]) during epileptic activity in Lennox-Gastaut syndrome (LGS) patients undergoing deep brain stimulation (DBS) surgery as part of the ESTEL (Electrical Stimulation of the Thalamus for Epilepsy of Lennox-Gastaut Phenotype) trial. Methods: Twelve LGS patients (mean age = 26.8 years) underwent bilateral CM-DBS implantation. Intraoperatively, simultaneous electroencephalogram (EEG) was recorded (range = 10-34 minutes) from scalp elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…We found that there is a statistically significant increase in gamma frequency that could be recorded on scalp EEG during the ictal period of head drops, a phenomenon that has been reported in other developmental and epileptic encephalopathies 9,11 . The presence of diffuse ictal cortical high frequency rhythms suggest recruitment of a widely distributed epileptic network, involving multifocal cortical areas and deep brain structures including thalamus and brainstem as reported in infantile spasms and Lennox–Gastaut syndrome 15 , 16 …”
Section: Discussionsupporting
confidence: 74%
“…We found that there is a statistically significant increase in gamma frequency that could be recorded on scalp EEG during the ictal period of head drops, a phenomenon that has been reported in other developmental and epileptic encephalopathies 9,11 . The presence of diffuse ictal cortical high frequency rhythms suggest recruitment of a widely distributed epileptic network, involving multifocal cortical areas and deep brain structures including thalamus and brainstem as reported in infantile spasms and Lennox–Gastaut syndrome 15 , 16 …”
Section: Discussionsupporting
confidence: 74%
“…16,18 All surgeries were performed under a modified anesthetic regimen combining intravenous remifentanil (0.1-0.3μg/kg/min) with inhalational isoflurane (0.5-0.7%), permitting intra-operative simultaneous EEG recordings from the thalamus and scalp. 19 Up to 1 day postoperatively, a brain computed tomography (CT) scan was acquired to confirm accurate DBS electrode positioning. DBS lead contact positions were established by coregistering postoperative CT to pre-operative MRI scans (see Fig 2).…”
Section: Methodsmentioning
confidence: 99%
“…The CM was identified preoperatively on patients’ 3T magnetic resonance imaging (MRI) scans using a magnetization‐prepared 2‐rapid‐gradient‐echoes (MP2RAGEs) sequence that was post‐processed using Sobel filtering to highlight intrathalamic borders, together with the 3‐dimensional Krauth/Morel thalamic atlas 17 that was nonlinearly spatially warped to each patient's brain 16,18 . All surgeries were performed under a modified anesthetic regimen combining intravenous remifentanil (0.1–0.3μg/kg/min) with inhalational isoflurane (0.5–0.7%), permitting intra‐operative simultaneous EEG recordings from the thalamus and scalp 19 . Up to 1 day postoperatively, a brain computed tomography (CT) scan was acquired to confirm accurate DBS electrode positioning.…”
Section: Methodsmentioning
confidence: 99%
“…However, controversy remains regarding whether the trigger of the epileptic seizures lies in the thalamus or cortex. For example, Dalic et al recently analyzed EEG findings in patients with Lennox-Gastaut syndrome (LGS) with simultaneous recordings from depth electrodes placed in the thalamic centromedian nucleus (CM) and scalp electrodes and found that most of the onsets of generalized fast activities were observed earlier in the scalp electrodes, whereas the onset of slow spikes and waves were variable [15]. Velasco et al analyzed the EEG onset of various types of seizures observed in patients with LGS using the depth electrodes placed in the CM and scalp electrodes and reported that the onset of generalized tonic, tonic-clonic, and atypical absence seizures occurred simultaneously in the CM and cortex; however, the EEG onset of myoclonic seizures was observed earlier in the CM [16].…”
Section: Discussionmentioning
confidence: 99%